(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
In recent years, technology has transformed business operations, with e-commerce platforms enabling customers to browse products, place orders, and complete transactions digitally. Traditional shopping methods, which rely on physical presence, manual billing, and limited operating hours, are often inefficient and prone to human error. This study presents Shopease, an integrated Python-based shopping cart system that combines user registration, product management, shopping cart functionality, checkout processing, and transaction tracking through a MySQL database. The system employs Object-Oriented Programming (OOP) principles and a GUI built with Tkinter and CustomTkinter to provide a user-friendly and interactive interface. Functional testing demonstrated that all modules, including login/registration, product catalog, shopping cart operations, checkout, and admin panel management, performed as expected. Shopease improves efficiency, accuracy, and accessibility compared to manual or console-based systems, offering a reliable platform for managing products, customers, and transactions in an educational or small-scale business environment. Limitations include the absence of online payment integration, delivery tracking, email notifications, and advanced security protocols, which provide opportunities for future enhancements.